2018
DOI: 10.1371/journal.pone.0193327
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure in children—Is living donor liver transplantation justified?

Abstract: ObjectivesLiving donor liver transplantation (LDLT) in patients with acute liver failure (ALF) has become an acceptable alternative to transplantation from deceased donors (DDLT). The aim of this study was to analyze outcomes of LDLT in pediatric patients with ALF based on our center’s experience.Material and methodsWe enrolled 63 children (at our institution) with ALF who underwent liver transplantation between 1997 and 2016. Among them 24 (38%) underwent a LDLT and 39 (62%) received a DDLT. Retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The baseline characteristics of the included studies are presented in Table 1. ( 5‐28 ) All of these studies were included in the systematic review; however, 15 studies with overlapping cohorts were excluded from the main meta‐analyses but may have been included in the sensitivity analyses. Outcome data were reported as 3‐year, 5‐year, and 10‐year posttransplantation patient and graft survival in acute and chronic liver failure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The baseline characteristics of the included studies are presented in Table 1. ( 5‐28 ) All of these studies were included in the systematic review; however, 15 studies with overlapping cohorts were excluded from the main meta‐analyses but may have been included in the sensitivity analyses. Outcome data were reported as 3‐year, 5‐year, and 10‐year posttransplantation patient and graft survival in acute and chronic liver failure.…”
Section: Resultsmentioning
confidence: 99%
“…The time origin of the survival analysis was not specified in 11 studies. ( 5,7­9,12,13,15,16,22,23,28 ) Three studies reported starting the analysis from the time of transplantation, one from the time of listing, and one from the time of donor evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our annual transplant rates for PALF have increased dramatically over the last 5 years, comprising 26% of all transplants in 2019—more than double most rates in international transplant programs 3,4 . The reasons for our higher than average transplant rates most likely reflect our “open‐door” policy for accepting referrals for any child in need of a liver transplant (irrespective of payer status); a broad referral base that includes children from all parts of South Africa and neighboring countries; and our efforts to increase the donor pool by using technical variant grafts from living donors, deceased donor reduced or split liver grafts, and performing ABO‐incompatible transplants, all of which avoid treatment delay 23,24 . Despite these considerations, it should be noted that the increased referral rate is a recent development and still in evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated improved graft quality from the LDLT compared with the DDLT, which also had higher rates of graft primary nonfunction. [ 29 ] Similarly, a 2016 Brazilian retrospective, single‐center study of 115 patients with PALF showed that LDLT was associated with a higher long‐term survival rate (72.4%) compared with DDLT (40.0%) as well as lower incidences of primary nonfunction. [ 30 ] The study also demonstrated improved waitlist mortality after the initiation of LDLT.…”
Section: Part I: Clinical Features Of Palfmentioning
confidence: 99%